El Yunque de México: del periodismo a la historia - Mario Virgilio Santiago Jiménez (Centre de Recherches sur les Mondes Américains, 2016)
In the early fifties of the twentieth century in Mexico, a secret, Catholic, anti-communist and anti-Semitic organization was born. At first it grew in universities and later in business and political spaces. Fifty years later its existence was revealed by journalists who have built a hegemonic version of its history.This paper questions three elements of journalistic version without interest definitively concluding the subject, trying to nurture the historical knowledge on Mexican rights, as well as establishing a healthy debate with investigative journalism.After a brief introduction, the three points are developed: first, that the origin of the group is part of a tradition; second, it has experimented changes over its history; and third, that its location between the rights requires greater precision.